ANALYSIS OF FACTORS THAT INFLUENCE STUDENTS' MATHEMATICAL CRITICAL THINKING SKILLS: INTRAPERSONAL INTELLIGENCE AND LEARNING MOTIVATION - Aswin Aswin; Dadan Dasari; Dadang Juandi; Surya Kurniawan (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
Mathematical critical thinking skills is a person's capacity that includes a thought process that aims to obtain a rational thought to do something or believe what will be done. Many factors influence students' mathematical critical thinking skills, including intrapersonal intelligence and learning motivation. This research points to control the stimulate of intrapersonal intelligence and learning motivation on students' mathematical critical thinking skills. This study is quantitative research through an ex-post-facto approach. The population in this research is a class XI high school in the Sidrap district. The quantity of samples in this research was 85 students who were selected by the purposive sampling technique. The data collection technique in this study used an instrument consisting of (1) an intrapersonal intelligence questionnaire, (2) a learning motivation questionnaire, and (3) a mathematical critical thinking ability questionnaire. Analysis of the data used is Structural Equation Modeling (SEM) using the PLS 3.0 smart computer program. The results of this study are that there is an influence between intrapersonal intelligence on students' mathematical critical thinking skills of 0.284 (P values = 0.039) and learning motivation affects students' mathematical critical thinking skills of 0,579 (P values = 0.00).